ASSESSMENT AND EVALUATION IN MODERN EDUCATION SYSTEMS - Evi Diyah Novita (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2025)
This article explores the evolving role of assessment and evaluation within modern education systems. As educational priorities shift toward developing 21st-century skills such as critical thinking, creativity, and collaboration, traditional assessment methods are increasingly being replaced or complemented by more formative, student-centered approaches. The integration of digital technologies has further transformed assessment practices, enabling real-time feedback, personalized learning, and greater accessibility. Additionally, there is a growing emphasis on inclusive and culturally responsive assessment strategies to support diverse learners. Through a qualitative review of recent literature and educational frameworks, this article discusses the benefits, challenges, and implications of these developments. The findings highlight the need for sustained professional development, policy reform, and collaboration among stakeholders to ensure that assessment remains relevant, equitable, and effective in supporting lifelong learning.